Book review: Ipshita Chanda, Selfing the City: Single Women Migrants and Their Lives in Kolkata. Issue 2 (December 2017) - Mahjebeen, Joanna
Ipshita Chanda, Selfing the City: Single Women Migrants and Their Lives in Kolkata . New Delhi: SAGE Publications; Kolkata: Stree Publications, 2017, 322 pp., ₹995.